Pendidikan Agama Islam dan Pengembangan Soft Skills Siswa - Muhammad Afit Imran; Amaluddin Amaluddin (Journal of Humanities, Social Sciences, and Education, 2025)
Islamic Religious Education (PAI) not only aims to shape students' religious knowledge, but also plays an important role in shaping character and developing soft skills that are crucial in community life. Soft skills such as communication, cooperation, leadership, empathy, and self-control are non-technical skills that are greatly needed in the 21st century. Through the approach of Islamic values ​​taught in PAI, students can internalize attitudes and behaviors that support the development of soft skills. This literature study aims to examine the contribution of PAI to the formation of soft skills in school students, by analyzing various scientific references and previous research results. The method used is a literature review by analyzing national and international journals related to PAI and soft skills. The results of the study show that PAI has a significant impact on the development of soft skills through the internalization of Islamic values, teacher role models, project-based learning activities and group discussions. These findings indicate the importance of strengthening contextual and reflective approaches in PAI learning. Thus, PAI has the potential to be a strategic forum in shaping students' personalities who are not only religious, but also adaptive, communicative, and collaborative in facing the challenges of the times.